2013
DOI: 10.1371/journal.pone.0054936
|View full text |Cite
|
Sign up to set email alerts
|

Xylella fastidiosa Differentially Accumulates Mineral Elements in Biofilm and Planktonic Cells

Abstract: Xylella fastidiosa is a bacterial plant pathogen that infects numerous plant hosts. Disease develops when the bacterium colonizes the xylem vessels and forms a biofilm. Inductively coupled plasma optical emission spectroscopy was used to examine the mineral element content of this pathogen in biofilm and planktonic states. Significant accumulations of copper (30-fold), manganese (6-fold), zinc (5-fold), calcium (2-fold) and potassium (2-fold) in the biofilm compared to planktonic cells were observed. Other min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 47 publications
7
51
1
Order By: Relevance
“…To our knowledge, this is the first study in which it was demonstrated that Zn alters the expression of genes involved in biosynthesis of EPS, augments EPS production, and affects culturability in a bacterium. However, the observed inhibition of growth caused by higher concentrations of Zn in the media is in agreement with previous reports (12,13,15,16). Zn tolerance/resistance are particularly significant for the X. fastidiosa life cycle, since Zn-containing fungicides (49)(50)(51)(52) and foliar Zn sprays are commonly used for fertilization (49,50,53), increasing the Zn content in the host.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To our knowledge, this is the first study in which it was demonstrated that Zn alters the expression of genes involved in biosynthesis of EPS, augments EPS production, and affects culturability in a bacterium. However, the observed inhibition of growth caused by higher concentrations of Zn in the media is in agreement with previous reports (12,13,15,16). Zn tolerance/resistance are particularly significant for the X. fastidiosa life cycle, since Zn-containing fungicides (49)(50)(51)(52) and foliar Zn sprays are commonly used for fertilization (49,50,53), increasing the Zn content in the host.…”
Section: Discussionsupporting
confidence: 93%
“…Although the metal induces a large increase in the production of EPS, most of the bacterial cells remain in the planktonic fraction in batch cultures. These results suggest that Zn promotes cell-to-cell attachment (shown previously by our group [13]) while it decreases surface-cell attachment. The former may be an important factor in the Zn-induced biofilm structures observed in microfluidic chambers after reinoculation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations